Voluntary STD Testing and Treatment Program at a Metropolitan Correctional Facility: Evaluation of Test Acceptability and Associated Risk Factors. (January 2014) - Brown, Christopher K.; Earley, Mary; Shaikh, Raees; Fickenscher, Jillian; Ott, Jessica; Person, Austin; Islam, K. M. Monirul; Simonsen, Kari; Sandkovsky, Uriel; Kaiser, Katherine Laux; Foxall, Mark; Margalit, Ruth
Few studies have addressed challenges of diagnosis and treatment of sexually transmitted diseases (STDs) within correctional facilities. Initiatives that screen all inmates can be cost-prohibitive, while symptom-based screening undoubtedly fails to recognize significant numbers of asymptomatically infected persons. This study discusses a voluntary STD screening and treatment program developed at the Douglas County (Nebraska) Department of Corrections where student volunteers interviewed, screened, and educated 456 inmates. Inmate urine samples and interview responses about risk behaviors and motivators for participation in the screening program were analyzed. The results support the ongoing project method to screen and treat inmates in the community correctional facility. Risk factor analysis suggests that targeted testing and treatment efforts may have a role in providing cost-effective care for STD among the incarcerated population.